Low-Grade Intraductal Carcinoma of the Lacrimal Gland. (April 2014) - Bursztyn, Lulu L. C. D.; Hyrcza, Martin D.; Allen, Larry H.; Berean, Kenneth W.; Wehrli, Bret
Abstract Intraductal carcinoma has been described in the salivary glands as a relatively benign tumour with low-grade histopathologic features. To our knowledge, this tumour has not previously been reported in the lacrimal gland. We report the first case of low-grade intraductal carcinoma occurring in the lacrimal gland. This tumour was discovered incidentally on neuro-imaging in an asymptomatic 65-year-old patient. Incisional biopsy revealed uniform, polygonal cells with eosinophilic cytoplasm and minimal nuclear atypia, arranged in solid, cribiform and micropapillary nests. The patient underwent complete surgical excision with no evidence of recurrence at 8 months of follow-up.